Climate information services for agro-pastoralists in Africa's Great Green Wall area - Diama, Agathe (International Crops Research Institute for the Semi-Arid Tropics, 2022)
Partnership signing ceremony Mali's Minister of Environment, Sanitation and Sustainable Development, Mr Modibo Koné, chaired the partnership signing event between ICRISAT, National Agency for the Great Green Wall, Mali’s Institute of Rural Economy, Mali-Météo and Orange-Mali for the use of climate information services by agro-pastoralists in the Great Green Wall area. This partnership is the logical continuation of the preliminary identification and development activities initiated with the support of the CGIAR Accelerating Climate Research Impact for Africa (AICCRA) and One CGIAR Initiative ClimBer